APPLICATION OF ENTITY FINANCIAL ACCOUNTING STANDARDS MICRO, SMALL AND MEDIUM IN LAYING HEN BUSINESS - Muwaddatu Tri Makhlusi; Dyah Pravitasari (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The main objective of this study is to provide a comprehensive understanding of the procedures involved in the preparation of financial reports specific to the poultry sector. This study investigates the difficulties Nurul Khumaida encounters in preparing financireports. The financial statements of Nurul Khumaida's poultry company will be compiled in accordance with the Financial Accounting Standards for Micro, Small, and Medium-sized Entities. This research uses a qualitative research methodology. In the data collection phase, various methodologies are used, such as observations, interviews, and documentation. The research investigates the financial reporting practices conducted by Nurul Khumaida in his poultry company, with special emphasis on income and expenditure accounts. The audited financial statements indicate inconsistencies with financial accounting standards applicable to micro, small, and medium-sized enterprises. The report also highlights the obstacles encountered in producing financial statements in accordance with these standards, highlighting the limited understanding among small and medium-sized enterprises of financial accounting standards. The financial statements of Nurul Khumaida's undertakings belonging to micro, small, and medium-sized enterprises will be compiled in accordance with the financial accounting rules specially designed for similar enterprises. The following statements will include financial status reports and loss reports. User texts can be re-formulated academically as follows: The language relates to declarations, i.e., those relating to financial issues, including financial statements and financial position reports